1992
DOI: 10.1104/pp.99.4.1686
|View full text |Cite
|
Sign up to set email alerts
|

Localized Patch Clamping of Plasma Membrane of a Polarized Plant Cell

Abstract: We used an ultraviolet laser to rupture a small region of cell wall of a polarized Fucus spiralis rhizoid cell and gained localized access to the plasma membrane at the growing apex. Careful control of cell turgor enabled a small portion of plasma membranebound cytoplasm to be exposed. (1,11,17,19,21), and more recently, the technique has been used to investigate their regulation (7,10,15,16,18,20).Removal of the cell wall to expose plasma membrane suitable for patch recording was predicted to be a major prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Fluorescence of injected cells was monitored at least 3 h after injection and recovery in SW. Photometric measurements of Ca 2ϩ were made on fura-2-dextran-injected rhizoid cells (19,20). For confocal imaging, zygotes were imaged after Ͼ3 h with a Bio-Rad (Hemel Hempstead, Hertfordshire, U.K.) 1024 confocal laser scanning microscope equipped with a Nikon ϫ40 (numerical aperture ϭ 1.3) oil immersion lens and an argon͞krypton laser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence of injected cells was monitored at least 3 h after injection and recovery in SW. Photometric measurements of Ca 2ϩ were made on fura-2-dextran-injected rhizoid cells (19,20). For confocal imaging, zygotes were imaged after Ͼ3 h with a Bio-Rad (Hemel Hempstead, Hertfordshire, U.K.) 1024 confocal laser scanning microscope equipped with a Nikon ϫ40 (numerical aperture ϭ 1.3) oil immersion lens and an argon͞krypton laser.…”
Section: Methodsmentioning
confidence: 99%
“…Fucus serratus embryos were cultured to the two-celled stage in seawater (SW) for 24 h in unidirectional white light at 17°C as described (19,20). Rhizoid cells were pressure microinjected with 10-50 M concentrations of dye prepared in artificial cytoplasm solution (19,20). Dyes used included fura-2-dextran (10 kDa), Calcium Green-dextran (10 kDa), or a mixture of Calcium Green-dextran and Texas Red-dextrans (10 kDa) (Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
“…Laser ablation of the cell wall to expose the plasma membrane has been used as a tool for investigations of algal cells (Taylor & Brownlee, 1992;DeBoer et al, 1994;Taylor et al, 1996) and higher plant cells (Kurkdjian et al, 1993;Henricksen et al, 1995); though only two studies have then successfully applied the patch-clamp technique to characterize ion channels in the exposed plasma membrane (Henricksen et al, 1995;Taylor et al, 1996). In the present study, we have shown that it is feasible to use the laser ablation technique to produce plasma membrane-bound blebs at defined locations along the hyphae of Aspergillus.…”
Section: Discussionmentioning
confidence: 99%
“…A pulsed nitrogen laser (VSL-337, Laser Science Inc., Cambridge, MA) was used to produce a high intensity u.v. beam into the microscope objective (Nikon UV-Fluor x 40, numerical aperture 0-8-1-3) and focused to a spot of c. 1 fim (see Taylor & Brownlee, 1992). The laser was triggered remotely using 12-V pulses from a stimulator.…”
Section: Growth Of Hyphae and Laser Microsurgerymentioning
confidence: 99%
See 1 more Smart Citation